Third-order ordinary differential equations equivalent to linear second-order ordinary differential equations via tangent transformations. (November 2016) - Nakpim, Warisa
Abstract: The linearization problem of a third-order ordinary differential equation by the tangent transformation is considered in the present paper. This is the first application of tangent (essentially) transformations to the linearization problem of third-order ordinary differential equations. Necessary and sufficient conditions for a third-order ordinary differential equation to be linearizable are obtained.